A First Record and Developmental Stages of an Exotic Species Cochlicellabarbara (Linnaeus, 1758) (Gastropoda-Cochicellidae) in Iraq Baghdad - Maysaloon Lafta Al-Doori (Journal of Global Pharma Technology, 2018)
The aim of this study is to highlight this species of gastropoda Cochlicellabarbara( Linnaeus, 1758), which is recorded for the first time in Iraq, which is an exotic animal in this country. It is a terrestrial Molluscan, the study for three months (February, March and April) 2017. In garden houses in Baghdad Al-Karkh, we studied the development stages from the egg to the adult, they lay a hundred of eggs in about (15-20) eggs in each gelatinous sac, the shell with 7 whorls and about 10 mm in length.Keywords: Mollusca, Gastropoda, First recorded, Cochlicellidae, Cochlicellabarbara.